SPORTS AND HEALTH ACTIVITIES: ESSENCE, CLASSIFICATION, AND TOOLS - ROMANENKO, SERHII (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The growing role of sports in society as a basis for health promotion requires active interaction of the population with the bodies of sports services. Under such conditions, the study of the essence and classification features of sports and health activities is necessary. The article aims to study the essence of the concept of "sports and health activities" and the disclosure of classification features and tools.Results. The importance of the concept of "sports and health activities" is investigated, and classification features and tools are revealed. The interpretation of the concepts of "sports and health service", "sports and health sphere," and "sports and health activities" by domestic scientists is revealed. Physical culture and sports activities differ in that the former is carried out for the development of material culture and the involvement of various groups in classes, and the latter is carried out by subjects of physical culture and sports for sports (children, youth, professional, Olympic and non-Olympic), sports for people with disabilities, etc.). If we unravel the educational institutions, then accordingly, we will use physical culture and health activities. If we talk about the population, their free time is about sports. We believe that society encourages independent sports to improve their health in the current context of the Kovid-19 pandemic and the transition of most educational institutions to distance learning. That is why the study of sports and health activities is more important. The author's interpretation of the concept of "sports and health activities" is defined which means the active interaction of society with objects that take into account the sports and health sphere, thus achieving the goal of strengthening health. Conclusions. The classification of sports and health activities is revealed. Sports and health activities are classified according to the following:The form of distribution of public consumption fundsThe motives for the production of servicesThe motives for consumptionThe degree of importance for the consumer and the content of the need met by consumptionThe list of classification features can be increased. The critical tendencies of sports and health-improving activity are determined. It is emphasized that the tools for developing sports and health activities should be formed based on basic content creation, marketing research to expand the range of potential consumers, and innovative communication strategies.
Keywords: sports and health service; sports and health sphere; sports and health activity; classification; tools